The Effect of Using Indonesian Standard Quick Response Code (QRIS) on Increasing Sales to Merchants in Pematangsiantar City - Silaen, Musa F.; Manurung, Sepbeariska; Nainggolan, Christine Dewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this research was to determine the effect of the use of The Indonesian Standard Quick Response Code (QRIS) on increased sales. This study uses descriptive quantitative by using primary data. Collecting data using a questionnaire with a Likert scale. The research variable consists of the perception of benefits (X1) and the easy perception (X2) while the dependent variable is sales (Y). The number of samples in this study was as many as 45 merchants in the city of Pematangsiantar. The results showed that the perception of benefits had a negative and insignificant effect on increased sales, while the perception of ease had a positive and significant effect on the increase in sales. The perception of benefits and the perception of convenience have a moderate correlation with increased sales. The perception of benefits and the perception of convenience have a moderate relationship with increased sales. Perception of benefits and easy perception contributed 24% in explaining the increase in sales, while the remaining 76% was influenced by other factors not studied in this research.